Estructura y dinámica de la conciencia moral en el proceso educativo - Mélich, Joan-Carles (Teoría de la Educación. Revista Interuniversitaria, 2009)
The aim of this work settles on describing, through the fenomenological methodology, the structure and dinamics of the moral conscience and its function in the educational process. The moral conscience, equally than the epistemologica! moral, is endowed of a temporary structure. Time, through its three dimensions (past, present, and future) allows the dialectics of the moral conscience. In the past the values are settled, in the present takes place the hermeneutics of reality, and in the future make an irruption the duty and the project. In the second part of this article, the author gets the moral conscience with the educational conscience together (in touch). Both are not identic, one cannot be reduced to the other. The main (basic) diference settles on the «technical question (matter)». Hence the educational conscience does not limit itself; like the moral one, to a hermeneutics of the present, but moreover it provokes and endeavours an «intervention» of the present, that is to say, a modification of the world.